Estrogen regulation of gene expression in the teleost fish immune system. (November 2016) - Burgos-Aceves, Mario Alberto; Cohen, Amit; Smith, Yoav; Faggio, Caterina
Abstract: Elucidating the mechanisms of estrogens-induced immunomodulation in teleost fish is of great importance due to the observed worldwide continuing decrease in pristine environments. However, little is know about the immunotoxicological consequences of exposure to these chemicals in fish, or of the mechanisms through which these effects are mediated. In this review, we summarize the results showing estrogens (natural or synthetic) acting through estrogen receptors and regulating specific target genes, also through microRNAs (miRNAs), leading to modulation of the immune functioning. The identification and characterization of miRNAs will provide new opportunities for functional genome research on teleost immune system and can also be useful when screening for novel molecule biomarkers for environmental pollution. Highlights: Estrogen on immune system represent a strategic control of diseases in aquaculture. Estrogen can regulate the expression of microRNAs. Estrogen can lead to modulation of expression of specific target genes.